A SYSTEMATIC REVIEW ON THE EFFECTIVENESS OF KETOENOLS AND THEIR RESISTANCE MECHANISM ON PHYTOPHAGOUS MITES OF THE TETRANYCHIDAE FAMILY - Emanuel Hernández Núñez; Esau Ruiz Sanchez; Dany Alejandro Dzib Cauich; Marcos Cua Basulto (Tropical and Subtropical Agroecosystems)
Background. Ketoenol acaricides exert their action by inhibiting Acetyl-CoA carboxylase (ACC). These acaricides have been highly effective for the management of phytophagous mites, however, their intensive use has generated resistant populations, which is why it is necessary to know what resistance mechanisms could be involved in mites of the Tetranychidae family in greenhouse and field conditions. Methodology. A literature review of ketoenolic acaricides was performed in the following databases: Google academic, Science Direct & Springer, for which word combinations were used such as: ketoenolic acaricides, tetronic and tetramic acid, spiromesifen, spirodiclofen, effectiveness of ketoenols, resistance mechanisms. Based on these parameters, 68 bibliographic references were selected, taking into consideration whether the studies had been carried out from year 2000 until 2023. To process the data from the publications, it was organized in the Microsoft Office Excel® program, where the information related to the effectiveness of ketoenolic acaricides and the resistance mechanisms of mites of the Tetranychidae family were classified, analyzed and discussed. Main findings. The use of Ketoenolic acaricides are an effective alternative in suppressing the population density of phytophagous mites of the Tetranychidae family in greenhouses and fields, taking into account that they are effective when applied at low or intermediate doses; likewise, the effectiveness of ketoenolic acaricides is not affected if they are applied in greenhouse and field conditions since their effectiveness is greater than 85%. On the other hand, resistance to ketoenolic acaricides is mainly mediated by metabolic resistance, due to high levels of activity of detoxification enzymes (P-450 monooxygenases, esterases and glutathione S-transferases) that the selected populations present. Regarding resistance at the site of action, there are few recorded cases, therefore, it is not considered an important factor in resistance to ketoenol acaricides in Tetranychidae. Implications. It is essential to know the mechanism of resistance to acaricides in Tetranychidae management programs, establishing more efficient measures on the use of chemical acaricides, such as a good application of acaricides to crops and rotation of acaricides, in this way we will contribute to a lower resistance to mites. Conclusion. This review indicates that ketoenolic acaricides are effective for control in mites, however, resistance to ketoenols in mites of the Tetranychidae family is mediated in most cases by detoxification enzymes.